Effect of Quercus infectoria and Zataria multiflora extracts on the expression of Apo-B100 and PPAR-α in liver and adipose tissues in insulin resistant rats - Mohammadi, Gholam Abbas; mohammadi Tahroodi, fariba; Fallah, Hossein; Bahar Moghaddam, Marzieh (Archives of Medical Laboratory Sciences, 2020)
Background: Insulin resistance can increase the risk of metabolic syndrome. Studies have shown that expression of PPAR alpha improved insulin function in patients with insulin resistance. Also ApoB100 is an essential ligand for the receptors of low-density lipoproteins (LDL). Increased plasma level of apoB100 is a risk factor for cardiovascular disease (CVD) and its increased production leads to insulin resistance. The aim of this study was to evaluate the effects of Q. Infectoria and Z. multiflora extracts on the expression of PPARα and Apo-B100 genes in adipose and hepatic tissues of insulin-resistant rats Materials and methods: Forty Wistar rats were divided into 1- healthy control, 2- high fat control, 3- fenofibrate,4- Q. Infectoria and 5- Z. multiflora groups. All groups were fed with high fat diet for 6 weeks expect for the healthy control. Glucose tolerance test was performed to confirm insulin resistance in rats. Then groups 3, 4, and 5 were treated by fenofibrate, Q. Infectoria and Z. multiflora extracts respectively. After sacrificing the rats, their liver and fat tissues were removed. Real-time PCR was used to assess PPARα and ApoB100 gene expressions. Results: All groups had significant weight gain after 8 weeks. Expression of PPAR-α and ApoB100 genes were the same in Q. Infectoria, Z. multiflora, fenofibrate and healthy control groups. Conclusion: In conclusion, Q. Infectoria and Z. multiflora extracts decreased ApoB100 and increased PPARα gene expressions but these changes were not statistically significant.